Plagiarism-Free Writing in Digital Learning Environments: How Possible Is It? - Phothongsunan, Sureepong (International Journal of Multidisciplinary in Management and Tourism, 2026)
What do EFL (English as a Foreign Language) students truly know about plagiarism? The issue of students’ plagiarism is rather serious in many contexts due to a paucity of knowledge and understanding of what it is. Many students are not aware of why it is intolerable in the academic community while some are without skills necessary to avoid it. To address this problem, this paper explores a collaborative digital platform designed to enable students to learn about the essence of plagiarism and to practice necessary skills, including summarizing, paraphrasing, and referencing. The study involved students enrolled in an academic writing course. The students worked on tasks and shared content through Google Workspace. During an informal feedback session, the students generally reported that working on the platform allowed them to gain a deeper understanding of plagiarism and improve their writing skills, particularly in summarizing, paraphrasing, and referencing. Overall, the study highlights the value of using collaborative digital learning approaches to foster plagiarism awareness and strengthen academic writing skills in contemporary learning environments.